Land Use Change and Carbon Stocks in the Toari Watershed - Kahirun, Kahirun; Baco S, La; Muhsimin, Muhsimin; Qadri, Saleh; Ardi, Ardi (Journal La Lifesci, 2024)
Changes in land use are linked to climate change, resulting in the loss of carbon reserves due to decrease in vegetated land. Forests play crucial role in carbon storage. This research aims to determine carbon storage in the Toari Watershed, Southeast Sulawesi, in response to land use changes. The method uses GIS analysis to track changes in land use from 1991 to 2023, employing the SRTM Digital Elevation Model (DEM) for delineation. Carbon storage is calculated by multiplying the area of each land use by its respective carbon content value. The results of this research show that there have been significant land changes occurring from 1991 to 2023. Forest land is the land use with the most extensive changes, experiencing decrease in area of 7,181.20 hectares. This was also followed by increased mixed dryland farming use by 5,579.23 hectares, plantations by 1,994.28 hectares, residential land by 353.13 hectares, and open land by 640.85 hectares. From 1991 to 2023, land use changes had big impact on carbon stocks in the Toari Watershed. The largest decrease occurred in secondary dryland forests, leading to reduction of 741,530.7 tons C. Conversely, mixed agricultural land and plantations saw increases of 167,376.90 tons C and 125,639.60 tons C, respectively. Open land and residential areas also registered increases in carbon stocks. These findings highlight the influence of land use on carbon stock changes. The carbon stocks in the Toari Watershed decreased from 1,142,112.3 tons C in 1991 to 728,627.9 tons C in 2023 due to changes in land use.